Load characterization in medium voltage of an electric distribution utility related to active filters - Corasaniti, Víctor Fabián (2006)
The behavior of the actual load of an electric energy distribution utility by means of voltage and current measurements is analyzed in this paper. Steady and transient states are taken into account. The main attention is fixed in points where present shunt compensation is installed. Results of field measurements and the connection and disconnection of capacitor banks are shown. Studies for future compensation are detailed and the possible advantages of active filter incorporation are analyzed in order to replace or complement the existing compensation. The minimal requirements are established in order to consider the design of the active filters and their compatibility with the existing installations.